Reprogramming of human fibroblasts into osteoblasts by insulin-like growth factor-binding protein 7. (6th January 2020) - Lu, ZuFu; Chiu, Joyce; Lee, Lucinda R.; Schindeler, Aaron; Jackson, Miriam; Ramaswamy, Yogambha; Dunstan, Colin R.; Hogg, Philip J.; Zreiqat, Hala
Abstract: The induced pluripotent stem cell (iPSC) is a promising cell source for tissue regeneration. However, the therapeutic value of iPSC technology is limited due to the complexity of induction protocols and potential risks of teratoma formation. A trans-differentiation approach employing natural factors may allow better control over reprogramming and improved safety. We report here a novel approach to drive trans-differentiation of human fibroblasts into functional osteoblasts using insulin-like growth factor binding protein 7 (IGFBP7). We initially determined that media conditioned by human osteoblasts can induce reprogramming of human fibroblasts to functional osteoblasts. Proteomic analysis identified IGFBP7 as being significantly elevated in media conditioned with osteoblasts compared with those with fibroblasts. Recombinant IGFBP7 induced a phenotypic switch from fibroblasts to osteoblasts. The switch was associated with senescence and dependent on autocrine IL-6 signaling. Our study supports a novel strategy for regenerating bone by using IGFBP7 to trans-differentiate fibroblasts to osteoblasts. : Abstract : Osteoblastic reprogramming by insulin-like growth factor-binding protein 7 (IGFBP7) and its application for bone tissue regeneration. Single protein (IGFBP7) treatment is sufficient to reprogram human fibroblasts into osteoblast-like cells partially via a mechanism of induction of a senescent phenotype and autocrine IL-6 signaling. These reprogrammed osteoblasts will have critical therapeutic implications to the patients with bone loss-related diseases.